Efficacy of aspirin for stage III colorectal cancer: a randomized double-blind placebo-controlled trial (JCOG1503C, EPISODE-III trial). (10th July 2019) - Miyamoto, Kenichi; Takashima, Atsuo; Mizusawa, Junki; Sato, Yuya; Shimada, Yasuhiro; Katayama, Hiroshi; Nakamura, Kenichi; Shibata, Taro; Fukuda, Haruhiko; Shida, Dai; Kanemitsu, Yukihide; Hamaguchi, Tetsuya; et al.
Abstract : A double-blind placebo-controlled phase III study for stage III colorectal cancer commenced in March 2018 to confirm the superiority of aspirin over placebo added to adjuvant chemotherapy after curative resection. Abstract: Adjuvant chemotherapy is the current standard treatment for stage III colorectal cancer after curative resection. However, the prognosis of stage III colorectal cancer is still poor even after curative resection and adjuvant chemotherapy. Several observational studies suggested that the anti-tumor effect of aspirin. Therefore, we planned a randomized double-blind placebo-controlled phase III trial, which commenced in Japan in March 2018, to confirm the superiority of aspirin over placebo added to adjuvant chemotherapy in terms of disease-free survival (DFS) for stage III colorectal cancer patients after curative resection. A total of 880 patients will be accrued from 20 Japanese institutions within 3 years. The primary endpoint is DFS and the secondary endpoints are overall survival, relapse-free survival, relative dose intensity, adverse events, and serious adverse events. This trial has been registered at Japan Registry of Clinical Trials as jRCTs031180009 (https://jrct.niph.go.jp/detail/589 ).